2020
DOI: 10.1088/1758-5090/ab7ef4
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinker length dictates step-growth hydrogel network formation dynamics and allows rapid on-chip photoencapsulation

Abstract: Hydrogels formed via free radical-mediated thiol-ene step-growth photopolymerization have been developed for a broad range of tissue engineering and regenerative medicine applications. While the crosslinking mechanism of thiol-ene hydrogels has been well-described, there has been only limited work exploring the physical differences among gels arising from variations in crosslinker properties. Here, we show that the character of linear polyethylene glycol (PEG) dithiols used to crosslink multi-arm polyethylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…In addition, all formulations had low coefficients of variation (CV 90% = 15%; CV 50% = 8%; CV 0% = 13%), indicating homogenous microgels especially when compared to batch emulsion or extrusion fragmentation techniques that typically result in higher levels of dispersity (e.g., CV ~30–40% for batch emulsions [ 15 ]; preliminary findings with inverse suspension polymerization resulted in CV ~70% ( Figure S16 )). The dispersity of particles formed here was within the range of that observed for other PEG-based microgels formed using microfluidic flow-focusing methods (CV = 5–20%) [ 19 , 49 ].…”
Section: Resultssupporting
confidence: 72%
“…In addition, all formulations had low coefficients of variation (CV 90% = 15%; CV 50% = 8%; CV 0% = 13%), indicating homogenous microgels especially when compared to batch emulsion or extrusion fragmentation techniques that typically result in higher levels of dispersity (e.g., CV ~30–40% for batch emulsions [ 15 ]; preliminary findings with inverse suspension polymerization resulted in CV ~70% ( Figure S16 )). The dispersity of particles formed here was within the range of that observed for other PEG-based microgels formed using microfluidic flow-focusing methods (CV = 5–20%) [ 19 , 49 ].…”
Section: Resultssupporting
confidence: 72%
“…Varying the flow ratio in a T-junction device tends to be more easily used to adjust the microspheroid AR than their diameter . In contrast for flow focusing and coflow junction designs, although it is also possible to control the AR, , changing the flow ratio is more likely to influence the final microspheroid diameter. , Due to the complex and resource-intensive nature of traditional microfluidic device fabrication, computational simulation has previously been done for a range of junction designs to provide researchers with a better understanding of the mechanisms controlling microspheroid geometries. − …”
Section: Resultsmentioning
confidence: 99%
“…40,41 Also, regulation of the size and swelling ratio depends on the density of cross-linking sites and the length of the cross-linker. [42][43][44] As discussed above, the optimum cross-linking density was provided by the PNVCL4 copolymer. The results of the elemental composition of PNVCL nanogels showed that the bromine content of the different nanogels was around 2% (Table S2, ESI †), so the length of the cross-linker should be the main factor to be considered.…”
Section: Effect Of the Cross-linker Length On The Gel Particle Size A...mentioning
confidence: 99%